2008
DOI: 10.1920/wp.cem.2008.2208
|View full text |Cite
|
Sign up to set email alerts
|

Does a pint a day affect your child's pay? The effect of prenatal alcohol exposure on adult outcomes

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(34 citation statements)
references
References 55 publications
1
33
0
Order By: Relevance
“…The capacity formation framework of Cunha and Heckman (2007) illustrates how childhood health could generate significant effects on subsequent health, educational attainment and labor market outcomes through dynamic complementarities and cross productivity with the development of cognitive and non-cognitive skills. An increasing number of design based studies have also found that early life health does not only influence adult health, but also educational attainments (Almond, Edlund and Palme, 2009) and labor market outcomes (Almond, 2006;Nilsson, 2008). By now, there is strong evidence on the link between parents' socio economic status and child health (c.f.…”
Section: Introductionmentioning
confidence: 99%
“…The capacity formation framework of Cunha and Heckman (2007) illustrates how childhood health could generate significant effects on subsequent health, educational attainment and labor market outcomes through dynamic complementarities and cross productivity with the development of cognitive and non-cognitive skills. An increasing number of design based studies have also found that early life health does not only influence adult health, but also educational attainments (Almond, Edlund and Palme, 2009) and labor market outcomes (Almond, 2006;Nilsson, 2008). By now, there is strong evidence on the link between parents' socio economic status and child health (c.f.…”
Section: Introductionmentioning
confidence: 99%
“…As a result, much of the empirical economics literature has used natural experiments to generate sharp, random shocks to foetal health conditions, either across space or cohorts 2 . Examples include disease outbreaks (Almond, 2006;Almond & Mazumder, 2005), in utero exposure to radioactive emissions (Almond, Edlund, & Palme, 2008;Otake & Schull, 1998) famine (Almond et al, 2007;Banerjee et al, 2007), fasting (Almond & Mazumder, 2008), and policy induced changes in alcohol consumption (Nilsson, 2008). This approach has successfully established long run effects of foetal health shocks.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, we are not the first to find such large effects: the few papers that attempt to deal with unobserved confounding in alcohol exposure also find large negative effects on child development (Nilsson, 2008;W€ ust, 2010;Zhang, 2010).…”
Section: Discussionmentioning
confidence: 85%
“…Although we argue that our IV estimates are an upper bound of the true causal effect, we are not the first to estimate such large effects, or to see a different association from the OLS after attempting to account for residual confounding. Indeed, Nilsson (2008) finds substantially large effects of prenatal alcohol exposure on human capital outcomes in Sweden. Similarly, Rosenzweig and Wolpin (1994) and W€ ust (2010) obtain considerably larger negative effects in within-mother specifications compared to more ambiguous results in the OLS or GLS.…”
Section: Resultsmentioning
confidence: 99%